Preparation and antifungal properties of monosubstituted zinc(П) phthalocyanine-chitosan oligosaccharide conjugates and their quaternized derivatives. (December 2018) - Tang, Feng-Xiang; Li, Hong-Cai; Ren, Xu-Dong; Sun, Ya; Xie, Wei; Wang, Cheng-Yu; Zheng, Bi-Yuan; Ke, Mei-Rong; Huang, Jian-Dong
Abstract: A series of novel conjugates between 1-[4-(2-carboxyethyl)phenoxy] zinc(II) phthalocyanine (1 ) and two kinds of molecular-weight chitosan oligosaccharides (COS1 and COS2) or their quaternized derivatives (QCOS1 and QCOS2) have been prepared and characterized. Their photophysical and photochemical properties, cellular uptake and in vitro photodynamic antifungal activity against Candida albicans have also been investigated. The conjugates, 1 -COS1 and 1 -COS2, exhibit excellent photodynamic inactivation capacity (IC90 10 μM), while the quaternized conjugates, 1 -QCOS1 and 1 -QCOS2, due to their less aggregation in aqueous media, higher singlet oxygen generation efficiency and cell uptake, achieve higher antifungal phototoxicity (IC90 5 μM). The COS molecular weight has no obvious effect on the antifungal activity. All of the conjugates are far superior to compound 1, which can be ascribed to the fact that the introduction of COS and QCOS onto phthalocyanine molecules can lessen their aggregation behavior, enhance their singlet oxygen generation efficiency and increase their cell uptake in aqueous media. More interestingly, quaternized conjugates show special affinity to the mitochondria of C. albicans and may induce apoptosis upon illumination. These results suggest that the quaternized conjugates, 1 -QCOS1 and 1 -QCOS2, are potential candidates for photodynamic antifungal therapy. Graphical abstract: Image 1 Highlights: A series of ZnPc-COS and ZnPc-QCOS conjugates have been prepared. The spectroscopic properties of conjugates in aqueous media have been discussed. The cellular uptake and photocytotoxicity increased after quaternization. ZnPc-QCOS conjugates shows the highest photocytotoxicity against C. albicans.